2004
DOI: 10.1111/j.0031-9317.2004.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase activity and proline accumulation in leaves and roots of olive trees in response to drought stress

Abstract: The olive tree (Olea europaea L.) is commonly grown in the Mediterranean basin and is able to resist severe and prolonged drought. Levels of proline (PRO) and malondialdehyde (MDA), and the lipoxygenase (LOX) activity were determined in 2-year-old olive plants (cv. 'Coratina') grown in environmental conditions characterized by high temperatures and high photosynthetic photon flux density levels and gradually subjected to a controlled water deficit for 20 days. Before and during the experimental period, leaf an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
141
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(162 citation statements)
references
References 50 publications
9
141
0
8
Order By: Relevance
“…We hypothesize that lipoxygenase activity in olive leaves can be significantly influenced by the climatic conditions. Lipoxygenase is more active in stressed plants and drought conditions (Sofo et al, 2004). Therefore, high levels of GLVs as of the first dates could be due to higher lipoxygenase activity, as the plants were in drought conditions for a long period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that lipoxygenase activity in olive leaves can be significantly influenced by the climatic conditions. Lipoxygenase is more active in stressed plants and drought conditions (Sofo et al, 2004). Therefore, high levels of GLVs as of the first dates could be due to higher lipoxygenase activity, as the plants were in drought conditions for a long period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high levels of GLVs as of the first dates could be due to higher lipoxygenase activity, as the plants were in drought conditions for a long period. During collection, mainly during the end of September and beginning of October, with increasing rainfall, GLVs and (Z)-3-hexen-1-ol acetate contents decrease drastically, because lipoxygenase can reduce its activity threefold in plants experiencing water availability (Sofo et al, 2004). Furthermore, LOX substrate (a-linoleic free fatty acids) could also be reduced, as olive leaves from irrigated olive trees reduce their linoleic acid content , thus influencing the LOX mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced generation of ROS in response to drought stress might activate some specific isoenzymes of LOX in water-stressed plants (Ye et al 2000). Sofo et al (2004) have suggested the existence of a strict relationship between the gradual increase of LOX activity and the progression of drought-stress conditions. Knowing that polyunsaturated fatty acids, the major component of cell membranes phospholipids is considered as the substrate of LOX, the enhancement of LOX activity has been noticed to damage cell membranes and destroy other cell components.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez et al (1994) found that rainfed olive roots were more concentrated around stem with longer distances than the irrigated olive roots. Root growth rate directly related to soil water content (Fernandez et al, 1994;Dichio et al, 2002;Sofo et al, 2004). Under stress conditions, the shoots lose more water than roots (Torrecillas et al, 1995).…”
Section: Discussionmentioning
confidence: 99%